PEMBUATAN ARANG AKTIF DARI TEMPURUNG KELAPA, SERBUK KAYU, TEMPURUNG DAN TANDAN KELAPA SAWIT - Gustan Pari; Sasa Abdurrohim (Jurnal Penelitian Hasil Hutan, 2003)
The aim of this experiment was to learn the properties/characteristics of activated charcoal manufacturedfrom various lignocellulosic materials, i.e. coconut shell, oilpalm bunches,  wood sawdust (sawn from mixed forest wood species), and empty oilpalm bunches.At first,  each  of the  four  lignocellulosic materials  was carbonized into charcoal  under the particular conditions, as follows : the  materials converted to small particles with 0.3 0.5  cm size, an  implementing carbonization temperature  at  500oC. The charcoal  was  activated  using  the condition:   activating temperature at 900oC for 30 minutes,  and exercising air flow  rate at 800 I,100oC. The variables implemented in this experiment were kinds of raw materials (i.e.  4 kinds as previously mentioned), and soaking  in 1 percent  NaOH (alkali) for 24 hours which was further compared with the one without soaking.Charcoal properties showed that coconut shell obtained the highest in fixed carbon content,  the lowest in volatile matter and ash.  Results in activated charcoal analyses showed that  coconut shell obtained  the highest  in yield  (50.5%)  while the empty fruit bunch was the lowest (29.3%).  The coconut shell also  obtained the   highest  in fixed  carbon  (85.9%)  while the lowest was saw  dust (69.1%).Soaking treatment showed better quality on most of activated charcoal properties.   Coconut shell gave the highest in benzene adsorption (20.17%) and iod adsorption (881.8  mg/g).  In general,  other raw materials showed low adsorption to benzene, while most of them has been met the AWWA B.600 78 standard or iod adsorption. The CPO refining showed that  saw dust activated charcoal gave the best  in refining (54.8% transmission)  followed by empty fruit bunch, coconut shell and oil palm shell.